Adenoid cystic carcinoma metastasized from the maxilla to the mandible: A case report. Issue 3 (May 2021) - Yokokawa, Misaki; Hirai, Hideaki; Cuong, Tran Minh; Fukuda, Shuhei; Sakamoto, Kei; Ikeda, Tohru; Harada, Hiroyuki
Abstract: Adenoid cystic carcinoma (ACC) is one of the most frequently occurring malignant tumors in salivary glands. Its clinical prognosis is poor with frequent distant metastasis. Herein, we describe the first reported case of ACC originating in the upper gingiva and metastasizing to the mandible. A 76-year-old Japanese man was diagnosed with cT4bN0M0 ACC of the left upper gingiva in 2005. He underwent total maxillectomy and was administered 50-Gy external beam radiotherapy. Five years after the surgery, he developed ACC of the left mandible. We recommended him to undergo segmental mandibulectomy, but he refused. We instead performed 50-Gy external-beam radiotherapy. However, rapid growth of the tumor was observed, he agreed to undergo surgery. We performed hemimandibulectomy and reconstruction using titanium plate and rectus abdominis musculocutaneous flap. Histopathologically, both tumors exhibited solid dominant ACC. No continuity was noted between each surgical margin. In addition, the mandibular lesion developed intraosseously. We diagnosed the mandible lesion of having metastasized from the upper gingiva. We must monitor patients with ACC using imaging examinations to detect recurrence or metastasis earlier to improve the prognosis.